Law and literature reconsidered - Sarat, Austin (Studies in law, politics, and society, 2008)
The purpose of this special issue of "Studies in Law, Politics, and Society" is to examine the situation of law and literature. Once hailed as a promising new way to think about law and as opening a vital conversation about literature the question today is whether the law and literature enterprise has lived up to its initial promise. Has it succeeded in establishing a new interdiscipinarity or lost energy as law and literature courses become part of the mainstream both in legal and literary studies? Has the study of law and literature given way or been incorporated into boarder interdisciplinary configurations? What, if any, new paradigms of literary study of legal phenomena are on the horizon?This is a contemporary study of law and literature. It includes contributions by an international group of leading scholars.